Problem aktywizacji społecznej i zawodowej romskiej mniejszości narodowej w Austrii na przykładzie miasta Oberwart - Osuch, Wiktor (Przedsiębiorczość - Edukacja, 2008)
The article presents the characteristics of Roma national minority in Austria with particularconsideration of social-economic activation issues of this nation. Many years of the poor levelof education, numerous prejudices and lasting stereotypes in Austrian society towards theRoma and in effect the high percentage of unemployment among this social group resulted intheir relegation to the peripheries of social and economic life. This publication shows numerousexamples of actions taken by federal authorities in Vienna, local governments, humanitarianorganizations, mass media as well as the help with projects financed by EU in overcomingbarriers and prejudices towards Roma minority in peripheral region of Burgenland in Oberwart (Austria). The project Mri Buti (My work) is the most important success of these actions. It gavepermanent employment to several dozen Roma families, but it is not a success for the interestedparty. The process of Roma activation seems to be a longterm process and more sophisticatedthan it was planned. The stereotypes and prejudices still play the crucial role, albeit significantlyless than in the past. Unfortunately traditions and numerous habits of this population group notalways give enough motivation to take actions and decisions and they are important barriers totaking economic activity and further education.